Analisis Kepuasan Masyarakat terhadap Pelayanan Rumah Sakit Umum Daerah R.A. Basoeni, Kabupaten Mojokerto Berdasarkan Ulasan di Google Maps Review - Mahqfiroh, Juliatul; Yuliaty, Farida (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2024)
Online review becomes more and more crucial in this rapidly evolving era. It is also play a significant role in influencing the decision making in healthcare service field. These online reviews provides a novel insight in how people are able to access, assess, and finally choose which healthcare facility to prefer to use. This study aims to analyze the online reviews and ratings made by the consumers available in Google Maps Review of Rumah Sakit Umum Daerah (RSUD) R.A. Basoeni Kabupaten Mojokerto, East Java. This study focuses in assessing the ratings and frequent keywords in the reviews which were made between 2019 and 2024. Rating 1 and 2 represent the negative reviews, 3 represent neutral, and 4 and 5 represent positive reviews. Negative reviews assessment showed the main user’s complaints include queue management, staff attitude, and the inadequate cleanliness of the facilities in RSUD RA. Basoeni. Positive reviews assessment highlighted the fast, friendly and professional services. This study emphasizes the need for hospital management to respond to reviewer complaints by improving the quality of facilities and providing training for staff as a means of increasing user satisfaction.